Assessment of competencies of postgraduate students for veterinary extension at Indian Agricultural Universities - MAHRA, GIRIJESH SINGH; KASHYAP, S K; BHARDWAJ, NEELAM; KAMESWARI, V L V; JOSHI, PRATIBHA; SINGH, G K (The Indian Journal of Animal Sciences, 2021)
In Indian content of National Agricultural Research and Education System (NARES), agricultural extension connects agricultural research and farmers. Post-graduate teaching in Extension discipline across all agricultural universities prepares students to transfer relevant technologies to farming community and to conduct need-based research by inculcating desired competencies among students. The present study primarily focuses on assessing the overall competency fulfilment level of postgraduate extension students with respect to veterinary extension. The acquisition level of core competencies among students was compared with importance level of respective competencies associated by Livestock Extension professionals. The investigation was based on primary data compiled from 30 livestock extension professionals working in Uttarakhand and 210 postgraduates (M.Sc. and Ph.D.) students across ten agricultural universities of northern India. It was found that ten core competencies related to veterinary extension which were perceived as highly important by Livestock Extension professionals had low acquisition level among students. Out of the ten universities examined for competency fulfilment, only two universities had high level of competency fulfilment while four universities had low level of competency fulfilment. The overall competency fulfilment index of all ten universities was 0.522 indicating a competency fulfilment of just above average with respect to identified 24 competencies. The competency fulfilment index developed can be utilized by agricultural universities for competency mapping of livestock extension professionals and students for further investigations.